Impact of cable bleeding towards cable characteristics and performance in VDSL2 ang g.fast technologies - Che Ku Alam, Che Ku Afifah (2020)
The application of copper cable in broadband services using very high-speed digital subscriber line transceivers 2 (VDSL2) (30a) has been proven to offer up to 50 Mbps upstream (US) and 100 Mbps downstream (DS) bandwidths at lower than 1 km distance. This application has been reckoned as a widely deployed broadband technology, with the latest G.fast technology being integral at present time, which can be attain 1 Gb/s for copper loops up to 250 m. That being mentioned, this project investigated the degradation in performance displayed by copper cable due to cable bleeding, thus contributing towards resistance and capacitance faults, along with varied configurations being simulated and measured. The simulated results were validated based on double-ended measurements performed via Vector Network Analyzer (VNA). A series of comparative studies had been carried out especially for attenuation between ideal and faulty conditions. These attenuation results were extracted to form resistance, capacitance, inductance, and conductance (RLCG) of a transmission line model. For ideal condition in 200 m measurement, the maximum achievable bit rate for VSDL2 was 29 Mbps for US and 79 Mbps for DS, along with estimation speed of G.fast technology in single pair at 662.5 Mbps. The measured and simulated results portrayed exceptional agreement with each other. Due to fault occurrence, the performance of the networks in terms of maximum achievable bit rate and speed performance had degraded. Significant degradation was noted to be the worst for solid cross faults (SCF) and complete open and cross (COC), in comparison to the ideal condition. The COC measurement showed that both US and DS were lower by 38% and 44%, respectively, when compared to those recorded for the ideal case. The general outcomes revealed that small faults had an impact on the performances of network transmission line based on the results of maximum achievable bit rate.